47 Assessing the value of listing essential medicines on population health outcomes for 126 countries. (18th July 2022) - Maraj, Darshanand; Steiner, Liane; Ikpeni, Oghevefejiro; Persaud, Nav
Abstract : Objectives: There is consensus that having access to timely and appropriate healthcare can improve health and prevent deaths. Medicines are an important part of effective healthcare but the extent to which medicine access actually leads to better population health is not known. Essential medicines lists are strategically used to facilitate equitable access to a select set of medicines both on a country and international levels. We examined the association between population health outcomes, relating to mortality causes considered amenable to healthcare, and the listing of specific medicines used to treat these causes on national essential medicines lists (NEMLs) of selected countries. Method: We conducted a cross-sectional study. We identified medicines used to treat 30 causes of death amenable to healthcare (outcome relevant medicines) and determined the total number of outcome relevant medicines listed on available countries' NEMLs. We used multiple linear regression to analyze the association between healthcare access and quality indices (health outcome scores) and the total number of outcome relevant medicines. An alternative regression analysis was also done using national life expectancy as the outcome measure. National gross domestic product (GDP) per capita and World Health Organization (WHO) geographical regions were controlled for in these analyses. Results: The total number of outcome relevant medicines listed by countries ranged from 27 to 402 (median: 180; interquartile range - IQR: 157 to 237). Across 126 countries, health outcome scores were associated with the number of medicines, GDP and WHO region (R 2 = 0.667). For every additional medicine listed, there was a 0.036 point increase in the outcome score (95% confidence interval - 95% CI: 0.001 to 0.071; p = 0.047); roughly corresponding to a 0.42 per 100, 000 deaths/year decrease in mortality. For every additional international dollar of GDP, there was 0.001 point increase (95% CI: 0.001 to 0.001; p <0.001) in outcome score and geographic associations showed more differences across Africa when compared to other regions ( p ranged from <0.001 to 0.024). In the separate regression with life expectancy, adding 1 medicine was associated with a 0.018 year increase in national life expectancy (95% CI: 0.004 to 0.032; p =0.010; n=124; adjusted R 2 =0.597). Conclusions: Listing outcome relevant medicines for causes of death considered amenable to effective healthcare, on NEMLs was associated with health outcome scores and separately, with national life expectancy, across countries with diverse incomes and geographic locations. This suggests that the selection of medicines listed on NEMLs is important for improving health outcomes. Future studies can use our research to identify which medicines should be included on NEMLs to improve health.